Research of Pearl Oyster Culture in Indonesia (2011-2021): A Bibliometric Analysis - Dewi Syahidah (Masyarakat Moluska Indonesia, 2022)
Pearl oyster is one type of mollusk that has great potential to be developed in several regions in Indonesia, such as West Papua, Maluku, Bali, and West Nusa Tenggara (NTB). The development of the marine and fisheries industry, including the pearl industry, is quite rapid, encouraging Indonesian scientists to conduct research and development related to the cultivation of the pearl oyster. To map the trend of pearl oyster research in Indonesia and the potential for further research, this paper explores research that has been carried out for ten years (2011-2021) based on the Google Scholar database through a bibliometric analysis, followed by visualization using the VOSviewer software. It was found that during the period, pearl oyster researchers were divided into 32 clusters and Cokrowati (4 documents) was the most dominating researcher in studying pearl oyster cultivation, followed by Ginting and Mukhlis (3 docs). The type of pearl oyster that has been most studied related to farming is pearl oyster (Pinctada maxima) and the penguin wing oyster shell (Pteria penguin). This study provides opportunities to develop research on both species.